INSPIRASI 'THE LEGEND OF THE BLUE SEA' DALAM PENERAPAN PADA TEKNIK TEKSTIL MANIPULATION - Rafaela Pasca Hariyanto; Christabel Annora Paramita Parung; Siti Zahro (Fashion and Fashion Education Journal, 2023)
The Covid-19 pandemic is a problem occured throughout the world and has an impact, especially on Indonesia. One of the consequences is the cultural change that occurred during before the pandemic, during the pandemic, and after the pandemic. Seeing the drastic cultural changes, it reminds of the Korean drama "The Legend of the Blue Sea" which tells the story of drastic cultural changes from the Joseon dynasty to modern times. Through cultural changes, there give new inspiration for the fashion sector. The aim of this study is to describe the stylization of the results of visual analysis inspired by the Korean drama "The Legend of the Blue Sea" which is a depiction of drastic cultural changes in the field of fashion. The method used in this research is practice-based research for the textile stylization process. The results of this research showed that the stylization process of visual analysis of "The Legend of the Blue Sea" can be processed into techniques applied to cloth for ready-to-wear collections. These techniques were pleats, flounce, layering, and ruffle. In addition, the colors contained in the image can also be applied to the appropriate material color.